Techno-Economic Comparative analysis of hybrid renewable energy systems optimization considering Off-Grid remote area electrification in Bangladesh - Himalay Baidya; Md Tarak Rahman Zisan; Arham Zaman Alif; Ahbab Ahmed; Mahmudul Hasan; Nahid-Ur-Rahman Chowdhury (Energy Conversion and Management: X)
Reliable electricity access is crucial for enhancing living standards, fostering socio-economic growth, and ensuring community well-being in remote and underserved regions. Bhasan Char, a remote island in the Bay of Bengal, faces significant challenges in providing sustainable and reliable energy to support its population of over 100,000 Rohingya refugees. For off-grid regions, Hybrid Renewable Energy Systems present a viable and environmentally sustainable electrification solution by integrating multiple energy sources. This study investigates the design, simulation, and optimization of HRES-based power generation to meet the comprehensive electricity needs of Bhasan Char. Using HOMER Pro software, six different hybrid energy models were developed and analyzed to evaluate their technical, economic, and environmental viability. Throughout the optimization process, peak loads of 2,287 kW, 470 kW, and 2,180 kW were considered for residential, community, and deferrable uses, respectively. Out of the six models evaluated, the most cost-effective configuration was found to be PV/Biogas/Diesel/Wind/Battery. This optimal solution comprises 3.5 MW of PV, 0.5 MW of biogas generator, 3.2 MW of diesel power, 1.98 MW of wind, 8.53 MWh battery storage capacity and can generate 14,893,809 kWh of energy annually, which is sufficient to meet the entire community’s energy requirements. With a Cost of Energy of $0.195/kWh and a Net Present Cost of roughly $34.9 million, the system presents an economically viable solution. The substantial 80.6 % penetration of renewable energy considerably reduces greenhouse gas emissions. Additionally, Sensitivity analyses were performed to explore the resilience of the proposed systems ensuring adaptability to future uncertainties. The research offers a viable model for rural electrification, providing valuable insights into deploying sustainable power solutions in isolated regions and supporting global objectives for energy transition.